2020
DOI: 10.1108/rpj-04-2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser power on formability, microstructure and mechanical properties of selective laser melted Mg-Al-Zn alloy

Abstract: Purpose This paper aims to study the effect of laser energy on the formability, microstructure and mechanical properties of AZ61D alloy to assist systematic study of laser additive manufacturing of magnesium alloys. Design/methodology/approach In this study, porous magnesium alloy samples were prepared by using different laser parameters. The changes of the formability and microstructure were observed by SEM, and the mechanical properties were tested. The above results were analyzed to obtain optimized laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The decreased mechanical response in the BD is likely due to oxidation and carbides from the graphite coatings on the feedstock rods becoming entrapped in layer interfaces [25], causing slight anisotropy in the bulk WE43 deposit. The observed anisotropy is similar to that reported in magnesium alloys created by beam-based AM methods [48]. Although the LD and BD do not perform as well as the WE43-T5 feedstock, the YS and UTS have a minimum increase of 41.6% and 3.5%, respectively, when compared to the WE43 as-cast material.…”
Section: Quasi-static Response Of Bulk We43 Depositsupporting
confidence: 83%
See 1 more Smart Citation
“…The decreased mechanical response in the BD is likely due to oxidation and carbides from the graphite coatings on the feedstock rods becoming entrapped in layer interfaces [25], causing slight anisotropy in the bulk WE43 deposit. The observed anisotropy is similar to that reported in magnesium alloys created by beam-based AM methods [48]. Although the LD and BD do not perform as well as the WE43-T5 feedstock, the YS and UTS have a minimum increase of 41.6% and 3.5%, respectively, when compared to the WE43 as-cast material.…”
Section: Quasi-static Response Of Bulk We43 Depositsupporting
confidence: 83%
“…Future research should investigate a deposition made in an inert atmosphere to mitigate oxidation effects and the strength regained when a T5 temper is applied to an as-deposited WE43 build. [48] 137 217 WE43 LPBF [14] 214.4 ± 3.54 250.9 ± 2.92 2.62 ± 0.29 * *-ASTM E8M-3856.…”
Section: Quasi-static Response Of Bulk We43 Depositmentioning
confidence: 99%
“…Also, a large fluctuation in hardness and elongation for LB-PBF parts was observed, which could be attributed to the inhomogeneous distribution of mechanical properties (Khorasani et al, 2017a(Khorasani et al, , 2017b(Khorasani et al, , 2017cChoi et al, 2017;Khorasani et al, 2017aKhorasani et al, , 2017bKhorasani et al, , 2017c. The effect of laser power on the mechanical properties of AZ61 alloy was studied by Wang et al (Wang et al, 2020). They found that higher laser power leads to an increase in the ultimate strength, but the best relative density was achieved with a laser power of 80 W. In this sense, for LB-PBF methods, the mechanical properties are a function of process parameters, powder particle size, printing strategy, preprocessing and the placement position of the components being built.…”
Section: Mechanical Properties Of Laser-based Powder Bed Fusionmentioning
confidence: 99%
“…Mn is one of the most conventional alloying elements in Mg alloys. In Mn-containing Mg-Al series magnesium alloys, Al 8 Mn 5 is the second common phase in addition to Mg 17 Al 12 [52,55,60,125,126]. It is reported that possible oxidation reactions in Mg-RE alloys, and indicated an oxygen affinity order of Y > Gd > Nd > Mg > Zr [131], confirming that Y 2 O 3 was the preferred oxide phase in AMprocessed Mg-RE alloy, which is consistent with the experimental observations.…”
Section: Phase Constituentmentioning
confidence: 99%